Structural and optical properties of novel nematogens based on DFT and semiempirical method—A comparative picture. (2nd July 2016) - Ojha, Durga P.
ABSTRACT: A comparative picture of structural, and optical properties of nematogens, viz., bis(4-propyloxyphenyl) 1, 12-dicarba-closo-dodecaborane-1, 12-dicarboxylate (Nematic1), and bis(4-butoxyphenyl) 1, 10-dicarba-closo-decaborane-1, 10-dicarboxylate (Nematic2) have been studied in ultraviolet (UV) and visible (Vis) regions. The structure of nematogens have been optimized using the Density functional B3LYP with 6–31+G (d) basis set using crystallographic geometry as input. The electronic structure of the molecules has been evaluated using the DFT, and semiempirical methods, namely; CNDO/S (complete neglect of differential overlap/ spectroscopy) and INDO/S (intermediate neglect of differential overlap/ spectroscopy). The HOMO (Highest Occupied Molecular Orbital)/LUMO (Lowest Unoccupied Molecular Orbital) energies, and oscillator strength (f) have also been reported using these methods. The electronic absorption spectra of the molecules have been simulated by employing the DFT method, semiempirical parameterizations. Molecular charge distribution and phase stability of these nematogens have been analyzed based on Mulliken and Loewdin population analysis. It has been observed that Nematic2 molecule shows the much flexibility for electronic transitions over a long wavelength region that leads to high photosensitivity.